Synchronization analysis of traffic lights using the software Synchro - Hernández Menéndez, Oisy (2020)
Traffic congestion is a problem that occurs worldwide, and Cuba is not exempt, even when the existing levels do not reach those reported by countries with high level of motorization. Signalized intersections in urban arteries of Havana are the most congested, which reflects negative impacts such as traffic accidents, delays, queue, and emission of pollutants into the atmosphere. A possible low-cost solution to decrease congestion is to coordinate the group of traffic signals. Therefore, this research aims to assess the efficiency of synchronized channels using parameters as cycle time, green intervals, and bandwidth for a case study using Synchro software. This research does not consider the minimization of delays of the users. The results support the feasibility of using these parameters to evaluate and select the design holding the most effective synchronization.